Biochemical, antioxidant and sensory evaluation of Davidsonia pruriens and Davidsoina jerseyana fruit infusion. (16th April 2021) - Nirmal, Nilesh Prakash; Mereddy, Ram; Webber, Dennis; Sultanbawa, Yasmina
Highlights: DP and DJ infusions consist of phenolics, minerals, organic acids and soluble sugars. High level of gallic acid was detected in DP and DJ infusions. Antioxidant capacities of DP, DJ and FF infusion were comparable. Sensory properties of DP and DJ infusions were compatible with FF infusion. Abstract: Davidsonia pruriens (DP) and Davidsonia jerseyana (DJ) are a gourmet bushfood with a sweet and sour taste. This study investigated the biochemical content, antioxidant activities, and sensory attributes of DP and DJ fruit infusions in comparison with commercial forest fruits (FF) infusion. Total phenolic and anthocyanin content was higher in FF infusion compared to DP or DJ fruit infusions (P < 0.05). An abundant amount of gallic acid was found in DP and DJ fruit infusions (P < 0.05). Quercetin, kaempferol-3-O-rutinoside, and peonidin-3-sambubioside was detected only in DP and DJ fruit infusions (P < 0.05). However, a high level of oxalic acid, minerals and soluble sugars were observed in FF infusions (P < 0.05). The antioxidant capacities and overall likeness score of DP or DJ infusion were comparable with the commercial FF infusion. Therefore, bioactive compounds, antioxidant activities and sensory properties suggested that DP and DJ fruit infusion have the potential to become a commercial health promoting drink.